Species richness and diversity of grassland plant communities and effects of nitrogen addition on some plant species - Sukhbat, Altangerel; Tuvshintogtokh, Indree; Tumenjargal, Tsogtsaikhan (Mongolian Journal of Botany, 2023)
From 2009-2022, we have in the vegetation communities of the long-term vegetation monitoring of the plant ecology and plant economy laboratory of the Institute of Botany in 3 settlements of the meadow steppe in the area of Mungunmorit sum of Tuv province, the dry steppe in the area of Tumentsogt sum of Sukhbaatar province, and the desert steppe plant community in the area of Dalanjargalan sum of Dornogovi province. A total of 108 plots of 1m2 were tested in three versions. In doing so, it was calculated to increase nitrogen in two different amounts: 28.57 g (N1) and 57.14 g (N2). The plots were fertilized with ammonium nitrate twice a year, during the first period of plant growth in May and during the peak period in July, to increase the richness and diversity of community species compared to the non-fertilized (N0) field. As a result of the research, in 2022, the species richness of the sedge field community in the N2 scenario with nitrogen supplementation was 1.2 times lower than the control N0 field (N0-S=75, N2-S=60), and the species diversity was 1.14 times (N0- H’=3.15, N2-H’=3.61) larger. In the dry steppe community, species richness is 1.1 times lower (N0-S=41, N2-S=37) and species diversity is 1.04 times lower (N0- H’=3.29, N2-H’=3.16) than the control N0 site. The species richness in the N1 scenario is 1.28 times lower (N0-S=9, N1-S=7) than in the N0 site of the barren steppe community, while the species richness is 1.2 times higher in the N2 scenario, and the species diversity is 1.2 times higher in the nitrogen N2 scenario (N0-H’= 1.86, N2- H’=2.2) increased respectively. 6 species of meadow steppe (Astragalus adsurgens, Carex pediformis, Chrysanthemum zawadskii, Cymbaria dahurica, Leuzea uniflora, Potentilla leucophylla), 3 species of dry steppe (Galium verum, Bassia prostrata, Potentilla strigosa), 2 species of desert steppe (Allium ramossum, Convolvulus ammanii) The addition of nitrogen had a statistically significant effect on the plant cover. In our study, the N2 scenario had a greater effect on the canopy of the above plants. Хээрийн ургамал бүлгэмдлүүдийн зүйлийн баялаг, олон янз байдал ба зарим зүйлийн ургамалд азотын нэмэгдлийн үзүүлэх нөлөө Хураангуй. Бид 2009-2022 онд тус хүрээлэнгийн Ургамалжлын экологи, ургамлын эдийн засгийн лабораторийн ургамалжлын урт хугацааны мониторингийн 3 суурингийн Төв аймгийн Мөнгөнморьт сумын нутаг дахь нугажуу хээр, Сүхбаатар аймгийн Түмэнцогт сумын нутаг дахь хуурай хээр болон Дорноговь аймгийн Даланжаргалан сумын нутаг дахь цөлөрхөг хээрийн ургамал бүлгэмдлүүдэд 1*1м2 хэмжээтэй нийт 108 талбайд 3 хувилбараар туршилт судалгааг явуулав. Ингэхдээ азотыг 28.57 г (N1) ба 57.14 г (N2) гэсэн 2 өөр хэмжээтэй нэмэгдүүлэхээр тооцож ургамал ургалтын эхний үе буюу 5-р сард, оргил үе буюу 7-р сард жилдээ 2 удаа аммоны нитратаар бордож, бүлгэмдлийн зүйлийн баялаг ба олон янз байдалд хэрхэн нөлөөлж байгааг бордоогүй (N0) талбайтай харьцуулан судлав. Судалгааны үр дүнд 2022 онд нугажуу хээрийн бүлгэмдлийн зүйлийн баялаг азотын нэмэгдэлтэй N2 хувилбарт хяналтын N0 талбайгаас 1.2 дахин бага (N0-S=75, N2-S=60), зүйлийн олон янз байдал нь 1.14 дахин (N0- H’=3.15, N2- H’=3.61) их байна. Хуурай хээрийн бүлгэмдэлд хяналтын N0 талбайгаас N2 хувилбарт зүйлийн баялаг 1.1 дахин бага (N0-S=41, N2-S=37), зүйлийн олон янз байдал нь 1.04 дахин (N0- H’=3.29, N2- H’=3.16) буурч байна. Цөлөрхөг хээрийн бүлгэмдлийн N0 талбайгаас N1 хувилбарт зүйлийн баялаг 1.28 дахин бага (N0-S=9, N1-S=7), харин N2 хувилбарт зүйлийн баялаг 1.2 дахин их, зүйлийн олон янз байдал азотын N2 хувилбарт 1.2 дахин (N0-H’=1.86, N2-H’=2.2) тус тус нэмэгдсэн байна. Нугажуу хээрийн 6 зүйл (Astragalus adsurgens, Carex pediformis, Chrysanthemum zawadskii, Cymbaria dahurica, Leuzea uniflora, Potentilla leucophylla), хуурай хээрийн 3 зүйл (Galium verum, Bassia prostrata, Potentilla strigosa), цөлөрхөг хээрийн 2 зүйл (Allium ramossum, Convolvulus ammanii)-ийн ургамлын тусгагийн бүрхцэд азотын нэмэгдэл статистикийн хувьд нөлөө үзүүлсэн. Бидний судалгаанд дээрх ургамлуудын тусгагийн бүрхцэд N2 хувилбар илүү нөлөө үзүүлж байв. Түлхүүр үгс: нугажуу хээр, хуурай хээр, цөлөрхөг хээр, азот, зүйлийн баялаг, олон янз байдал